EXERCICE 1B.3 - Développer puis réduire :
A = (2x + 1)² – (x + 3)² B = (2x + 3)² – (x – 7)(x + 7) C = (x + 2)(x – 2) – (x – 3)² D = (x – 5)² – (2x – 7)(x – 5) E = (3x + 1)(x – 2) – (2x – 3)²

MERCI

2

Réponses

2013-12-23T17:40:57+01:00
A=(2x+1)²-(x+3)²
A=4x²+4x+1-(x²+6x+9)
A=4x²+4x+1-x²-6x-9
A=3x²-2x-8

B=(2x+3)²-(x-7)(x+7)
B=4x²+12x+9-(x²+7x-7x-49)
B=4x²+12x+9-x²-7x+7x+49
B=3x²+12x+58

C=(x+2)(x-2)-(x-3)²
C=x²-2x+2x-4-(x²-6x+9)
C=x²-4-x²+6x-9
C=6x-13

D=(x-5)²-(2x-7)(x-5)
D=x²-10x+25-(2x²-10x-7x+35)
D=x²-10x+25-2x²+10x+7x-35
D=-x²+7x-10

E=(3x+1)(x-2)-(2x-3)²
E=3x²-6x+x-2-(4x²-12x+9)
E=3x²-6x+x-2-4x²+12x-9
E=-x²+7x-11
2013-12-23T17:49:23+01:00
Développer et réduire :

A = (2x + 1)² - (x + 3)²
A = 4x² + 4x + 1 - (x² + 6x + 9)
A = 4x² + 4x + 1 - x² - 6x - 9
A = 3x² - 2x - 8

B = (2x + 3)² - (x - 7) (x + 7)
B= 4x² +12x + 9 - (x² + 7x - 7x - 49)
B = 4x² +12x + 9 - x² - 7x + 7x + 49
B = 3x² +12x + 58

C = (x + 2) (x - 2) - (x - 3)²
C = x² - 2x + 2x - 4 - (x² - 6x + 9)
C = x² - 4 - x² + 6x - 9
C = 6x - 13

D = (x - 5)² - (2x - 7) (x - 5)
D = x² - 10x + 25 - (2x² - 10x - 7x + 35)
D = x² - 10x + 25 - 2x² + 10x + 7x - 35
D = -x² + 7x - 10

E = (3x + 1) (x - 2) - (2x - 3)²
E = 3x² - 6x + x - 2 - (4x² - 12x + 9)
E = 3x² - 6x + x - 2 - 4x² + 12x - 9
E = -x² + 7x - 11